2020
DOI: 10.1109/access.2020.3007322
|View full text |Cite
|
Sign up to set email alerts
|

Improving Bus Transit Services for Disabled Individuals: Demand Clustering, Bus Assignment, and Route Optimization

Abstract: Bus transit provides shorter-distance public transportation services, which are subject to various disability discrimination acts with various dedicated features. The Americans with Disabilities Act (ADA) requires that disabled individuals shall have equal rights to receive fare bus transit services, including fixed-route and door-todoor bus services. Most previous studies were mainly focused on policy aspects as part of the efforts of disability rights. The proper planning of demand requests from disabled ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Since the 1990s, a number of researchers have studied the hazardous waste recycling logistics system, most of which are related to the coordination of facility location and transportation route optimization problem [3]. Zografos and Samara [4] were the first to propose hazardous waste location and routing model, in which they constructed three objectives including transport duration, transport and disposal risk.…”
Section: Hazardous Waste Location-routing Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the 1990s, a number of researchers have studied the hazardous waste recycling logistics system, most of which are related to the coordination of facility location and transportation route optimization problem [3]. Zografos and Samara [4] were the first to propose hazardous waste location and routing model, in which they constructed three objectives including transport duration, transport and disposal risk.…”
Section: Hazardous Waste Location-routing Problemmentioning
confidence: 99%
“…This example sets up 15 production sites of waste household appliances (No. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15], and each 3 candidate nodes for collection center, recycling center, and processing center (No. [16][17][18][19][20][21][22][23][24].…”
Section: Basic Examplementioning
confidence: 99%
“…There are many variants of VRP [6,19,25]. However, there are three streams of literature related to our work, namely the two-echelon vehicle routing problem (2E-VRP), the electric vehicle routing problem (EVRP), and the two-echelon electric vehicle routing problem (2E-EVRP).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Constraints (18) ensure the flow balance at each satellite, which means the total amount of goods received by a satellite from the depot equals that shipped from the satellite to customers. Constraints (19) ensure that each customer is visited only once in the second echelon. Constraints (20) guarantee that the capacity of the trucks is not exceeded.…”
Section: Dantzig-wolfe Decompositionmentioning
confidence: 99%
“…Some scholars also took the passenger flow between subway stations as the weight of connecting edges, and evaluated and analyzed the destructresistance of Chengdu subway network by calculating the bearing pressure between nodes with different strength and connecting edges [8,12,19,26,35]. Some scholars to the site through the line between the number of public transport networks in Shanghai as the edge weights of the node clustering coefficient and correlation study found that the whole Shanghai passenger flow distribution is more uniform but local distribution difference is bigger, the node degrees obey exponential distribution and site saturated flow and its connection is superlinear density [9,15,24,37]. Chen obtained the travel time of conventional bus and rail transit stations with the help of GPS technology and GIS technology and took it as the weight.…”
Section: Research On Urban Weighted Traffic Networkmentioning
confidence: 99%